2014
DOI: 10.1159/000356306
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Is Associated with Dental Fear in Childhood: Findings from a Birth Cohort Study

Abstract: Objective: This study aimed to investigate the prevalence of dental fear in preschool children and to estimate its association with maternal and children characteristics. Methods: The study was nested in a population-based birth cohort from Pelotas, Brazil, started in 2004. A sample of 1,129 children aged 5 years was dentally examined, and their mothers were interviewed. Dental fear was investigated using a validated instrument through the question ‘Do you think that your child is afraid of going to the dentis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(85 citation statements)
references
References 34 publications
6
64
0
6
Order By: Relevance
“…Dental caries occurrence may be influenced by socioeconomic, demographic, behavioral, biological and clinical conditions and avoidance to look for dental treatment is one major reason for the impairment of oral health (2). In dentistry, fear has been reported to be a significant aspect affecting attendance to dental care, since anxious people tend to avoid dental offices (3). The presence of dental fear in childhood may be a problem even for latter periods of life, because this feeling may persist for a long time (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries occurrence may be influenced by socioeconomic, demographic, behavioral, biological and clinical conditions and avoidance to look for dental treatment is one major reason for the impairment of oral health (2). In dentistry, fear has been reported to be a significant aspect affecting attendance to dental care, since anxious people tend to avoid dental offices (3). The presence of dental fear in childhood may be a problem even for latter periods of life, because this feeling may persist for a long time (4).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between child's gender and dental fear is not completely unveiled, with contradictory results exhibited by the literature (9). Children's dental experience has also an important impact in dental fear occurrence, with higher prevalence observed in children who had never visited the dentist, who had frequently experienced dental pain and whose reason for the first dental visit was curative or urgency (3,7,8). Also, dental fear can influence the behavior of children during dental treatment and this is especially important for pediatric dentists, who need their cooperation when carrying out dental treatments (3).…”
Section: Introductionmentioning
confidence: 99%
“…11 Dental anxiety and dental fear are often referred to synonymously, and their presence in early childhood has been associated to the maternal oral condition, the presence of dental caries, and dental pain. 12 A negative dental experience can create dental fear, and, consequently, avoidance of a dental appointment and poor oral health conditions. 13 Previous results have shown that dental anxiety is related to general anxiety and high levels of general fearfulness.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of children dental fear is multifactorial (current dental caries, current dental pain, previous history of dental treatment, family experiences, environmental characteristics, family socioeconomic status and mothers' dental attitudes) [21].…”
Section: Discussionmentioning
confidence: 99%